Physical and Mechanical Characterization of Sugarcane Bagasse Particleboards for Civil Construction - Battistelle, Rosane A. G. [UNESP]; Fujino, Danielle M. [UNESP]; e Silva, Ana L. C. [UNESP]; Bezerra, Barbara S. [UNESP]; Valarelli, Ivaldo de D. [UNESP] (Int Centre Sustainable Dev Energy Water & Env Systems-sdewes, 2016)
In the worldwide market of particleboard production, the use of alternative raw materials is increasing, due to high demand and lack of traditional raw material, despite efforts of reforestation. In Brazil, the main agricultural commodity is sugarcane due to the copious production of sugar and ethanol. In the state of Sao Paulo alone approximately 140 million tons of sugarcane bagasse are produced every year, from which around 70% is burned for energy production, not adding value to the residue and generating pollution to the environment; and the other 30% is sold for composting. The objective of this work is to add value to the sugarcane bagasse by using it as a raw material for particleboard production to be employed as flooring in the area of civil construction. To achieve this, the present research characterized the physical and mechanical characteristics of the particleboards with the following alternative raw materials: sugarcane bagasse and leaves of bamboo. Particleboards were produced to reach high density (0.8 g/cm(3)) using the resin (bi-component) polyurethane castor oil. Tests for abrasion, roughness and resistance to denting and wear (Janka hardness) verified that the addition of leaves of bamboo in the mixtures, contrary to what was expected, did not confer a greater degree of resistance to the particleboards. Lastly, the results showed that sugarcane bagasse is a viable raw material alternative for the production of particleboards, intended to be used as products and flooring.
Keywords: Sugarcane bagasse; Solid waste; Recycling; Particleboard